Studi Literatur: Efektivitas Deteksi Malaria Menggunakan Pemeriksaan Mikroskopis Apusan Darah - Charisma, Acivrida Mega; Ekawasti, Fitrine; Azis, Mutiara Zakhilah; Sari, Adela Permata; Suci, Azlin Eva; Putra R, Rafi; Putri, Sintia Cahyani; Sugiarto, Agus Bambang (Jurnal Kedokteran Universitas Palangka Raya, 2025)
Malaria is an infectious disease caused by the parasites Plasmodium malariae, Plasmodium vivax, Plasmodium, falciparum, Plasmodium ovale, and Plasmodium knowlesi. The purpose of the literature review is to determine the effectiveness of malaria detection microscopically using blood smears. This research method uses data from scientific publications sourced from PubMed, ScienceDirect, and Google Scholar. Malaria cases in 2019-2021 have increased worldwide. Deaths from malaria that occurred worldwide in 2019-2020 increased by 12%. Indonesia contributes the second largest number of malaria cases in the Asian region after India, especially in the eastern region including Papua Province, West Papua Province, East Nusa Tenggara Province, and Maluku Province. Mortality rates from malaria still occur in several provinces in Indonesia. The purpose of this study is to determine the effectiveness of malaria detection using microscopic examination of blood smears. This research method is a literature review of the description of research results that have been conducted by others. Searches on the Google Scholar and Science Direct search engines use boolean techniques. This journal review was taken because the detection of malaria using blood smear microscopic tests is one of the most commonly used common methods, and can help improve professional competence in diagnosing and planning appropriate treatment for malaria sufferers, so it is relevant for doctors, analysts, and health researchers. Blood smear microscopy is the main way to detect malaria using thick blood preparations, this test can find Plasmodium malariae, Plasmodium vivax, Plasmodium, falciparum, Plasmodium ovale, Plasmodium knowlesi even in small amounts. Thin blood preparations help identify parasite species accurately.